Effects of low carbohydrate diet compared to low fat diet on reversing the metabolic syndrome, using NCEP ATP III criteria: a randomized clinical trial - Sherzad Ali Ismael (BMC, 2021)
Abstract Introduction The purpose of this study is to compare the change in the metabolic syndrome prevalence and risk factors between participants who followed a low carbohydrate diet and those who followed a low fat diet for six months in Erbil city/ Iraqi Kurdistan. Methods Out of 289 apparently healthy obese adults who were chosen by a stratified multistage probability sampling method, 94 of them agreed to participate in the study. They were assigned to low carbohydrate and low fat diet groups. Both groups were followed up for 6 months and the data were taken at baseline, after 3 months and after 6 months of intervention. Ninety-four obese adults completed the intervention. One-way repeated measures ANOVA was used to compare differences of metabolic dependent variables between the two independent variables, the low carbohydrate and low fat diet, at baseline, after 3 months and after 6 months of intervention. Results The Participants in low carbohydrate diet group had greater decrease in the prevalence of MetS. At the baseline, according to the ATP III criteria, the prevalence of metabolic syndrome was 44.4% (24/54) in low carbohydrate diet group and 60% (24/40) in low fat diet group. The prevalence of MetS was decreased significantly to 16.7% (9/54) after 3 months and to 3.7% (2/54) after 6 months in low carbohydrate diet (p < 0.001). Moreover, the prevalence of MetS was decreased significantly to 32.5 (13/40) after 3 months and to 22.5% (9/40) after 6 months in low fat diet (p < 0.001). No statistically significant difference was found between low carbohydrate diet & low fat diet at the baseline (p-value = 0.136) and after 3 months and after 6 months of intervention. Conclusions Both low carbohydrate diet and low fat diet have significant effects on reducing the prevalence of MetS in obese adults when followed up for 6 months. Compared to low fat diet, low carbohydrate diet had greater effect in reducing the prevalence of metabolic syndrome. Both diet programs were found to be effective in improving the metabolic state of obese adults. Trial registration The trial is registered retrospectively at the US National Institutes of Health ( ClinicalTrials.gov ). The registration in the US National Institutes of Health was done in 23/12/2020 with the registration number: NCT04681924 .